Potensi Kebangkrutan Pada Sektor Perbankan Syariah Untuk Menghadapi Perubahan Lingkungan Bisnis - Dwi Nuraini Ihsan; Sharfina Putri Kartika (ETIKONOMI, 2015)
Potential Bankruptcy On Islamic Banking Sector Facing Business Environmental Changes This research aims is to evaluate the soundness of Islamic banks and to predict the bankruptcy potency from the Islamic banks. The methods that used on this paper are RGEC method and the modified altman z-score analysis. The RGEC is represents by NPF, LR, risk profile, ROA, NCOM, and CAR. The altman z-score is represents by the ratio of networking capital to total asset, retained earning to total asset, earning before interest and tax to total asset, and book value of equity to book value of debt. The result shown that the Islamic bank’s soundness used RGEC methods is fit into healthy category in 2010-2014 periods.  The altman z-score also show that the Islamic banks fit into safe zone in 2010-2014 periods.DOI: 10.15408/etk.v14i2.2268